A platform technology for generating subunit vaccines against diverse viral pathogens - Young, Andrew; Isaacs, Ariel; Scott, Connor A. P.; Modhiran, Naphak; McMillan, Christopher L. D.; Cheung, Stacey T. M.; Barr, Jennifer; Marsh, Glenn; Thakur, Nazia; Bailey, Dalan; Li, Kenneth S. M.; Luk, Hayes K. H.; et al. (Frontiers in Immunology, 2022)
The COVID-19 pandemic response has shown how vaccine platform technologies can be used to rapidly and effectively counteract a novel emerging infectious disease. The speed of development for mRNA and vector-based vaccines outpaced those of subunit vaccines, however, subunit vaccines can offer advantages in terms of safety and stability. Here we describe a subunit vaccine platform technology, the molecular clamp, in application to four viruses from divergent taxonomic families: Middle Eastern respiratory syndrome coronavirus (MERS-CoV), Ebola virus (EBOV), Lassa virus (LASV) and Nipah virus (NiV). The clamp streamlines subunit antigen production by both stabilising the immunologically important prefusion epitopes of trimeric viral fusion proteins while enabling purification without target-specific reagents by acting as an affinity tag. Conformations for each viral antigen were confirmed by monoclonal antibody binding, size exclusion chromatography and electron microscopy. Notably, all four antigens tested remained stable over four weeks of incubation at 40 °C. Of the four vaccines tested, a neutralising immune response was stimulated by clamp stabilised MERS-CoV spike, EBOV glycoprotein and NiV fusion protein. Only the clamp stabilised LASV glycoprotein precursor failed to elicit virus neutralising antibodies. MERS-CoV and EBOV vaccine candidates were both tested in animal models and found to provide protection against viral challenge.